Nutrition Assistance, Household Economic Relief, and Maternal Well-Being: A Qualitative Study of the Free Nutritious Meal Program in Bekasi, Indonesia - Indri Widiawati; Veranus Sidharta (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines how breastfeeding mothers perceive the Free Nutritious Meal Program (MBG) as nutrition assistance, household economic relief, and support for maternal well-being in Perwira Village, Bekasi, Indonesia. Using a descriptive qualitative case study design, data were collected through in-depth interviews, observation, and documentation involving three breastfeeding mothers and two posyandu cadres. The data were organized and interpreted through NVivo-assisted coding, data condensation, categorization, and thematic analysis. The findings show that beneficiaries perceived MBG positively because it provided ready-to-consume meals, reduced breakfast expenses, saved preparation time, and eased morning domestic burdens. Mothers also associated the program with better nutritional intake, maternal stamina, perceived breast milk quality, infant health, and stunting prevention. Posyandu cadres played a central role in beneficiary identification, information dissemination, food distribution, data updating, and complaint handling. However, several constraints limited program effectiveness, including monotonous menus, inconsistent food freshness, changing distribution schedules, limited nutrition education, and communication gaps. The study concludes that MBG can strengthen maternal and child welfare when food provision is integrated with nutrition literacy, predictable services, dignified communication, and systematic beneficiary feedback. These improvements are essential for sustainable community-based nutrition policy and household resilience.